Dentists' Perspectives on Commercial Practices in Private Dentistry. (January 2022) - Holden, A.C.L.; Adam, L.; Thomson, W.M.
Background: Dentistry is predominantly provided in a commercial context in Australia. Despite this, little is known about how dentists navigate potential tensions that may arise between commercial and professional obligations in private dental practice. This analysis uses a qualitative approach to explore dentists' perceptions and attitudes toward the commercialized nature of private dental practice and how these affect their professional role in providing care. Methods: Participants were recruited by advertising on social media, as well as through a professional association and a corporate dental group's graduate training program. Data were collected from participants through interviews and written reflections. The data were subjected to thematic analysis to reveal deeper meanings and linkages between different emergent themes. Results: Twenty dentists who worked in private practice environments were recruited to take part. The analysis revealed the following themes within the data: dentistry devalued, commercial influences on professional behavior, the effect of advertising and competition on dentistry, ethical selling, and the impacts of commercialism on consumers of dentistry. Conclusions: Consumers of dentistry may only be superficially empowered by the commercialized context of private dental practice. Empowerment to decide which services to access and from whom does not address the inherent disparities that exist within the dentist-patient clinical relationship. Advertising and the active "selling" of oral health services are all designed to create dental consumers, not to empower them. While advertising might assist patients to understand available treatments, the primary objective of marketing is not health education. Increasing competition and consumer choice within dentistry may help to empower consumers of dental services but only if the dentist-patient relationship remains founded in altruistic intent, with the doctrine of "caveat emptor" (buyer beware) having no place within dentistry. Knowledge Transfer Statement: This research provides novel insights into how dentists experience the commercial context of private dental practice and how this is perceived to be both beneficial and detrimental to the consumers of dental services. This work will help to guide policy development to address the commercial determinants of oral health generated by the nature of commercialized dental practice environments.